Perencanaan Pengembangan Kawasan Ekonomi Khusus Batam - Citra Watti Mena Simatupang; Dompak, Timbul (Dialektika Publik, 2024)
In a regional autonomy in Batam City, it has imposed dualism of authority where there is a Batam City Government (Batam City Government) and the existence of Batam Business Entities (BP Batam). Based on dualism, this authority has an issue which will lead to harmony between the two institutions. That way, the government has also not been able to try to solve the problem. So that there is one strategy taken, namely by making Batam a Special Economic Zone (SEZ).). Based on the above, the purpose of this study is to analyze the overlap of the authority of the Batam City Government and Batam Entrepreneur Agency related to the development of Special Economic Zones. This research includes policy research that uses a descriptive method of qualitative approach. What has been explained is an event of overlapping authority in government administration and its impact on the development of the Special Economic Zone in Batam. From this research on data collection can be done based on the results of interviews, documents, websites, journals, and news. Based on the intended explanation, overlap in an authority can be from several aspects such as permits, land, spatial planning, forests, and assets. That way the overlap can hamper a special economic zone. The solution to this is to form a division of authority from the working area or zoning so that it becomes clear the workspace of BP Batam and the Batam City Government